PREPARATION AND CHARACTERIZATION OF GREEN GOLD NANOPARTICLES INHIBITING K562 CELL APOPTOSIS - UMESH KUMAR PARIDA; S. K. BISWAL; B. K. BINDHANI (International Journal of Pharma and Bio Sciences, 2014)
Eco-friendly synthesis of nanoparticles, which is one of the most advanced evergreen branches of nanoscience for biomedical application. This synthesis is non toxic and very low cost are major features of production it further attractive prospective option for biomedical field and elsewhere. In this investigation, the anticancer potentiality of AuNPs, stabilized with Olea europaea L was studied in K562 cell line. Metallic AuNPs were prepared by reducing with ethanolic Olea europaea L extract. The green synthesis of AuNPswas characterized and evaluated by UV-visible Spectroscopic, XRD, FTIR, TEM, DLS and biological activities using various biochemical assays. Green synthesis of AuNPs was confirmed by instrument method. AuNPs were decreased the growth and viability of the K562 cell line and increased the apoptosis.